Research methods in information - Pickard, Alison Jane; Childs, Susan (Susan M.) (London: Facet Publishing, 2013)
The long-awaited 2nd edition of this best-selling research methods handbook is fully updated and includes brand new coverage of online research methods and techniques, mixed methodology and qualitative analysis. There is an entire chapter contributed by Professor Julie McLeod, Sue Childs and Elizabeth Lomas focusing on research data management, applying evidence from the recent JISC funded'DATUM' project. The first to focus entirely on the needs of the information and communications community, it guides the would-be researcher through the variety of possibilities open to them under the heading'research' and provides students with the confidence to embark on their dissertations. The focus here is on the'doing' and although the philosophy and theory of research is explored to provide context, this is essentially a practical exploration of the whole research process with each chapter fully supported by examples and exercises tried and tested over a whole teaching career. The book will take readers through each aspect of the research process including: the major research paradigms reviewing the literature defining the research the research proposal sampling research ethics methods including case studies, surveys, experimental research, ethnography, Delphi study, action research, historical research and grounded theory collection techniques including interviews, questionnaires, observation, diaries, focus groups, usability testing, qualitative and quantitative data analysis software for analysis virtual research presenting the research It is essential reading for students of information and communications studies and archives and records management, and will be an invaluable handbook for practitioners beginning a piece of research
Includes bibliographical references : page [329]-345) and index.
Keywords: Information science -- Research -- Methodology